Emplacement conditions and exhumation of the Varvarco Tonalite and associated plutons from the Cordillera del Viento, Southern Central Andes - Assis, Omar (2021)
Fil: Assis, Omar. Instituto de Geociências, Universidade de Brasília, Laboratório de Geocronologia e geoquímica isotópica. Brasil.